تأثير العوامل الديموغرافية والوظيفية على ضغوط العمل لدى أساتذة جامعة الجزيرة السودان - صالح، عصام عمر فضل; حامد، عثمان تاج السر مساعد; عثمان، عامر عبدالوهاب أحمد; عبدالله، عمران عباس يوسف (جامعة الجزيرة - عمادة الدراسات العليا والبحث العلمي, 2013)
Job stress is considered as a part of studying of recent organization in social science. Tthe main objective of this study is to study the impact of employment and demographic factors on joP stress among the staff of the university of the Gezira. The study followed the descriptive analytical methodology using SPSS method. The main findings of the study is: there are highly significant correlations at 0.05 level of significance between the employment and demographic variables and job stress except for the nature of work, in addition to when the univirsity staff members are feeling theire occupation is not make job safety for them, then the job pressure level will be increased. The study recommened that, more statistics studies should be conducteded in other acadmic settings including basic and secondary schools teatchers in Sudan.
يعتبر موضوع ضغوط العمل مدخلاً من المداخل المعاصرة لدراسة المنظمات الحديثة في العلوم الاجتماعية. هدفت الدراسة إلى دراسة أهم المتغيرات الديمغرافية والوظيفية التي تؤثر على ضغوط العمل لدى هيئة التدريس بجامعة الجزيرة. اتبعت الدراسة المنهج الوصفي التحليلي باستخدام برنامج الحزم الإحصائية للعلوم الاجتماعية SPSS)). توصلت الدراسة إلى أن المتغيرات الوظيفية والديمغرافية وعوامل بيئة العمل لها ارتباط معنوي عند مستوى معنوية 0.05 مع ضغوط العمل ماعدا طبيعة العمل، بالإضافة إلى أن هيئة التدريس الجامعي عندما تشعر بأن وظيفتها لا تقدم لها الأمان الوظيفي يزداد مستوى ضغط العمل لديها. من أهم توصيات الدراسة إجراء مزيد من الدراسات الإحصائية في هذا المجال في أوساط تعليمية أخرى كالتعليم الثانوي وتعليم الأساس في السودان.
Keywords: التعليم العالي -- جامعة الجزيرة -- هيئة التدريس -- ضغوط العمل